Ultrahigh strength nanocomposite hydrogels designed by locking oriented tunicate cellulose nanocrystals in polymeric networks. (15th September 2020) - Hu, Danning; Cui, Yande; Mo, Kangwei; Wang, Junmei; Huang, Yanan; Miao, Xiaran; Lin, Jinyou; Chang, Chunyu
Abstract: Hydrogels consisting lots of water resemble the human soft tissues, but their disordered structures and weak mechanical properties usually limit their biomedical applications. Herein, a facile strategy to prepare highly ordered nanocomposite hydrogels with ultrahigh strength is reported, where the oriented tunicate cellulose nanocrystals (TCNCs) were locked in polymeric networks. Firstly, a stretchable supramolecular hydrogel was prepared by loosely crosslinking adamantine moiety contained polymers with β -cyclodextrin modified TCNCs through host-guest interaction. Subsequently, dual physically cross-linked hydrogel was constructed by introducing Fe 3+ ions into the pre-stretched supramolecular hydrogel for the formation of coordination bonds and freezing of oriented TCNCs. The resultant hydrogels exhibited ultrahigh tensile strength, elastic modulus, and toughness, along the direction of pre-stretching. The aligned TCNCs as both multifunctional cross-linking agents and interfacial compatible reinforcements of dual physically cross-linked networks largely contributed to the excellent mechanical performance of nanocomposite hydrogel. Our findings provide a universal method for designing hydrogels with highly ordered architectures and outstanding mechanical performances as potential biomimetic materials for biomedical applications. Highlights: A new strategy was used to fabricate nanocomposite hydrogels with high performance. Tunicate cellulose nanocrystals were aligned by prestretching and locked by electrostatic interaction in hydrogel networks. The resultant hydrogels showed anisotropic structure and ultrahigh mechanical strength.